Enhancing critical thinking through guided discovery learning in distance medical education in Papua - Samdei Carolina Rumbino; Elisa Nugraha Haryadi Salakay; Doni Widyandana; Titi Savitri Prihatiningsih (Jurnal Konseling dan Pendidikan, 2025)
Medical education in Papua faces unique challenges, especially in enhancing students’ critical thinking through distance learning. This study aimed to develop a Guided Discovery Learning (GDL)-based student worksheet and evaluate its effectiveness in improving critical thinking skills. Employing a Research and Development (R&D) design with a mixed-method approach that integrated both quantitative and qualitative data. The study involved 184 first, third, fifth, and seventh-semester medical students in Papua. Instruments included validated critical thinking tests based on Facione’s indicators, worksheet assessment rubrics, and student response questionnaires. Data were analyzed using paired sample t-tests and thematic analysis. The results showed a significant increase in student’s critical thinking post-test scores (mean = 62.45) compared to pre-test scores (mean = 37.00). Students also gave positive responses to the GDL-based worksheets. This indicates that GDL-based worksheets are effective instructional tools for fostering critical thinking in remote education settings. The study contributes to educational practice by introducing an adaptable method suitable for under-resourced regions. However, limitations include infrastructural barriers and a small sample size, which may affect generalizability. Future research should involve a broader population and explore long-term impacts.